UMPSA opens more help desks for prospective students, easing university admission process - Mimi Rabita, Abd Wahit (UMPSA, 2024)
PEKAN, 19 September 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) is extending support to students in need of financial assistance and other resources to facilitate the admission process, ahead of the registration day set for September 28.